The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1001/archpsyc.57.8.761
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dorsal and Orbital Prefrontal Gray Matter Volumes in Schizophrenia

Abstract: Background: Converging neuroanatomic, neurophysiological, and neurobehavioral evidence implicate prefrontal subregions in schizophrenia. Neuroanatomic studies with magnetic resonance (MR) imaging enable regional volume parcellation. Inconsistent reports may relate to variable methods and small samples. We attempted to resolve volume differences within sectors of the prefrontal lobe in a large sample, relating volumes to clinical and neurocognitive features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
193
5
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 346 publications
(224 citation statements)
references
References 74 publications
20
193
5
2
Order By: Relevance
“…They reported that the white matter reduction was most severe in the orbitofrontal region. Gur et al (2000) reported an association, in women schizophrenic subjects only, between decreased orbital (gray matter) volumes and negative symptoms. In the current sample, we also found a significant correlation between total SANS scores and left frontal gray matter volume in schizophrenic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the white matter reduction was most severe in the orbitofrontal region. Gur et al (2000) reported an association, in women schizophrenic subjects only, between decreased orbital (gray matter) volumes and negative symptoms. In the current sample, we also found a significant correlation between total SANS scores and left frontal gray matter volume in schizophrenic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed abnormalities in prefrontal metabolism and impairment in executive function have been documented in a wide range of disorders including those with dopaminergic involvement such as drug addiction, schizophrenia, Parkinson's disease and ADHD (Volkow et al, 1993b;Gur et al, 2000;Robbins, 2007;Zgaljardic et al, 2006).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The sample overlaps with samples reported in earlier publications (18)(19)(20). The current dataset includes all SCZ patients, their family members, and demographically balanced HC who have been studied on the same scanner with the same protocol and who had suitable quality of scan for automated analysis of the entire supertentorial brain.…”
Section: Participantsmentioning
confidence: 99%